The Challenge of the New PNS Pension Scheme in Indonesia: Pay as You Go to Be Fully Funded - Mahir Pratama; Lina Miftahul Jannah (Universitas Teuku Umar, 2023)
The increase in the number of civil servants retiring every year and the high life expectancy makes the pension fund increase every year. With the pay as you go scheme currently implemented, the APBN's fiscal burden is even higher. For this reason, the government plans to change the civil servant pension system to a fully funded system. The purpose of this research is to look at the challenges in implementing a fully funded scheme for civil servant pensions in Indonesia. The research method uses a postpositivist approach with primary data obtained from interviews with informants from members of the DPR RI legislature in the field of finance, experts from Commission XI DPR RI and public policy researchers. Secondary data were obtained from literature studies, documents and relevant government reports for analysis. Data processing techniques with open coding, axial coding and selecting coding with illustrative analysis assisted by NVivo12 plus software. The results of the study show that the government must reform pension fund management institutions, pay close attention to the investment climate, transition data on new schemes that need to be regulated by the ministry for the utilization of the state apparatus, the national staffing agency, the ministry of finance and local governments. In addition, this fully funded policy requires consistency over a long period of time to have an impact on the state budget and education for civil servants. In anticipating a new pension scheme, the government needs to prepare a roadmap for the weaknesses of the fully funded scheme, especially aspects of investment risk and civil servant pension insurance.